Beginning Shell Scripting - Foster-Johnson, Eric; Welch, John C; Anderson, Micah (Programmer to programmer, 2005)
Covering all major platforms-Linux, Unix, Mac OS X, and Windows-this guide shows programmers and power users how to customize an operating system, automate commands, and simplify administration tasks using shell scriptsOffers complete shell-scripting instructions, robust code examples, and full scripts for OS customizationCovers shells as a user interface, basic scripting techniques, script editing and debugging, graphing data, and simplifying administrative tasksIn addition to Unix and Linux scripting, the book covers the latest Windows scripting techniques and offers a complete tutorial on Mac OS X scripting, including detailed coverage of mobile file systems, legacy applications, Mac text editors, video captures, and the Mac OS X Open Scripting Architecture.